Fraser syndrome: features suggestive of prenatal diagnosis in a review of 38 cases1. (9th December 2016) - Tessier, Aude; Sarreau, Mélie; Pelluard, Fanny; André, Gwenaelle; Blesson, Sophie; Bucourt, Martine; Dechelotte, Pierre; Faivre, Laurence; Frébourg, Thierry; Goldenberg, Alice; Goua, Valérie; Jeanne‐Pasquier, Corinne; et al.
Abstract: Objective: Fraser syndrome (FS) is a rare malformation recessive disorder. Major criteria are cryptophtalmos, syndactyly, respiratory, genital and urinary tract anomalies. Few prenatal presentations have been reported. Method: We analyzed the prenatal and postnatal fetal phenotype in 38 cases of FS, including 25 pregnancy termination cases, 8 intra‐uterine death cases and 4 cases that died after birth. Results: Including both prenatal and postnatal fetal phenotypic evaluation, all cases presented dysmorphic features with nose and ear dysplasia. Renal anomalies and syndactyly were present in 37/38 cases, cryptophtalmos in 36/38, airways anomalies in 30/37 and genital anomalies in 30/35 cases. Anomalies of the abdominal wall such as low set umbilicus and omphalocele were found in 31 cases. Among the 26 cases for which ultrasound data were available, detectable anomalies included oligohydramnios (22), ascites/hydrops (9), renal anomalies (20), evidence for high airways obstruction (11), ophthalmologic anomalies (4), ear dysplasia (2) and syndactyly (2). Conclusion: This study shows that the postnatal phenotype of FS is very specific, whereas oligohydramnios hampers the prenatal recognition of the cardinal FS diagnosis criteria. Association of oligohydramnios, kidney agenesis and CHAOS should lead to consider this diagnosis. © 2016 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Fraser syndrome (FS) is a rare recessive disorder. Major criteria are cryptophtalmos, syndactyly, respiratory and genito‐urinary tract anomalies. The post‐natal phenotype is very specific but few prenatal presentations have been reported. What does this study add? This study analyzes the prenatal ultrasound and/or postnatal fetal phenotype in 38 cases of FS and shows that cardinal postnatal diagnosis criteria are rarely found on prenatal ultrasound. Association of oligohydramnios, kidney agenesis and CHAOS should lead consideration of this diagnosis.